A study to observe the association of left ventricular ejection fraction and wall motion score index with duration of early systolic lengthening in patients with non-ST-elevation acute coronary syndrome - Dayanand Paswan,; Lipika Adhikari,; Sandip Sarkar, (Asian Journal of Medical Sciences, 2024)
Background: Management of non-ST elevation myocardial infarction acute coronary syndrome (NSTEMI ACS) patients is not well defined as that of ST elevation myocardial infarction. The accuracy of results of conventional echocardiography is significantly compromised when imaging is suboptimal, myocardial damage is in small areas, and compensatory hyperkinesias of healthy segment. Aims and Objectives: Duration of early systolic lengthening (DESL) may be employed to identify early myocardial ischemia and thus, may help to prepare treatment strategies for NSTEMI patients. Materials and Methods: A total of 57 patients with NSTEMI ACS attending the cardiology department were included in the study group. Results: More than 80% of patients of NSTEMI have normal or near normal ejection fraction and wall motion score index. In our study, the DESL is prolonged in a significant number of non-ST-elevation acute coronary syndrome patients. Conclusion: As DESL is afterload independent, it is superior to global longitudinal strain in assessing myocardial damage. Several studies including ourselves show that DESL of <50 ms may be the cutoff value to reveal minimal myocardial damage.